2019
DOI: 10.1155/2019/4842592
|View full text |Cite
|
Sign up to set email alerts
|

Oleic Acid Protects against Hepatic Ischemia and Reperfusion Injury in Mice by Inhibiting AKT/mTOR Pathways

Abstract: Hepatic ischemia-reperfusion (I/R) injury is a serious complication in patients who have undergone hepatic surgery such as orthotopic liver transplantation and partial hepatectomy. Recently, a new cytoprotective agent, ursodeoxycholyl lysophosphatidylethanolamide (UDCA-LPE), was reported to protect against hepatic I/R injury. However, the protective mechanism of UDCA-LPE is not fully understood. Therefore, we conducted this study to explore its underlying mechanism. We used liquid chromatography-tandem mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…To determine the effect of PPARγ, some researchers used PPARγ agonist rosiglitazone and connecting peptide to treat mice, which decreased the occurrence of IRI [69]. PPARγ has a protective effect on IRI, which increases the level of SOD and H 2 O 2 hydrolase, decreases the level of nicotinamide adenine dinucleotide phosphate oxidase, slows down the degradation of Bcl-2 and Bcl-xl, and significantly reduces the phosphorylation level of AKT to inhibit p65 nuclear translocation and inflammatory response [70][71][72]. Besides, peroxisome proliferatoractivated receptor γ coactivator 1α (PGC-1α) is a major regulator of mitochondria and ROS, which promotes the release of a series of antioxidant enzymes to resist oxidative injury [73].…”
Section: Protective Mechanisms Of Irimentioning
confidence: 99%
“…To determine the effect of PPARγ, some researchers used PPARγ agonist rosiglitazone and connecting peptide to treat mice, which decreased the occurrence of IRI [69]. PPARγ has a protective effect on IRI, which increases the level of SOD and H 2 O 2 hydrolase, decreases the level of nicotinamide adenine dinucleotide phosphate oxidase, slows down the degradation of Bcl-2 and Bcl-xl, and significantly reduces the phosphorylation level of AKT to inhibit p65 nuclear translocation and inflammatory response [70][71][72]. Besides, peroxisome proliferatoractivated receptor γ coactivator 1α (PGC-1α) is a major regulator of mitochondria and ROS, which promotes the release of a series of antioxidant enzymes to resist oxidative injury [73].…”
Section: Protective Mechanisms Of Irimentioning
confidence: 99%
“…Moreover, oleic acid has been confirmed to be more steatogenic, though less apoptotigenic, than palmitic acid in hepatocytes cell cultures [ 43 ]. Recent findings have demonstrated that mice pretreated with oleic acid improved their tolerance to hepatic I/R injury [ 44 ]. The proposed mechanism is that oleic acid could be able to downregulate the AKT/mTOR phosphorylation pathway and the consequent p65 nuclear translocations needed to initiate the inflammatory response [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have demonstrated that mice pretreated with oleic acid improved their tolerance to hepatic I/R injury [ 44 ]. The proposed mechanism is that oleic acid could be able to downregulate the AKT/mTOR phosphorylation pathway and the consequent p65 nuclear translocations needed to initiate the inflammatory response [ 44 ]. These findings help to justify the low susceptibility of MCD livers to prolonged cold preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with oleic acid (OA) improved the tolerance of mice undergoing hepatic I/R injury by downregulating the phosphorylation of AKT and oxidative stress. An in vitro study showed that OA effectively inhibited oxidative stress, inflammation and cell death in hydrogen peroxide (H 2 O 2 )-treated HepG2 cells by upregulating autophagy 59. Other investigations showed that plant extract pretreatment attenuated hepatic I/R injury via inhibition of autophagy and apoptosis.…”
mentioning
confidence: 99%